The new churches in a parish of immigrants of the great Lima - Marzal, Manuel (1987)
I gather in this article a small part of a forthcoming book on the religious paths of Lima immigrants in the Virgen de Nazaret parish, which covers more than half of the population of the El Agustino district. When immigrants arrive in Lima, many adapt to the new religious situation by going more or less regularly to Catholic temples, but many others experience a certain religious transformation through three paths: some reproduce the peasant religion in the city, especially with the "recreation" of the patron saint festivals, others join "base communities" of the parish, to better understand the bible and seek greater commitment to social change, and others end up enrolling in one of the sects or new churches , which are proliferating in recent years in the young towns of the great Lima. This article is limited to analyzing the third way, for which I will deal successively with the growth of the new churches, the reasons why immigrants convert and the sociopolitical dimension of the new churches.